2020
DOI: 10.1038/s41598-020-67447-y
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragmentation modifies the composition of bumblebee communities and modulates their trophic and competitive interactions for pollination

Abstract: Understanding the effects of landscape fragmentation on global bumblebee declines requires going beyond estimates of abundance and richness and evaluating changes in community composition and trophic and competitive interactions. We studied the effects of forest fragmentation in a Scandinavian landscape that combines temperate forests and croplands. for that, we evaluated how forest fragmentation features (patch size, isolation and shape complexity, percentage of forest in the surroundings) as well as local fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 84 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…It was observed that along with abundance and richness, the composition of the bumblebee communities also changed during the eight-year study. We concluded with Gomez-Martinez [ 37 ] that species adapted to forest habitats decreased in number with forest fragmentation, while species related to open areas become more abundant.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was observed that along with abundance and richness, the composition of the bumblebee communities also changed during the eight-year study. We concluded with Gomez-Martinez [ 37 ] that species adapted to forest habitats decreased in number with forest fragmentation, while species related to open areas become more abundant.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have shown that while some species have considerably declined in fragmented habitats, others have remained relatively abundant. Habitat fragmentation can affect the diversity of bumblebee species and communities, and may depend, among other aspects, on their habitat preferences, foraging ranges, and behavioural patterns [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fragmentation effects on other trophic levels also influence plant community dynamics, which may contribute to differences between observation and simulation. Edge effects on pollinator composition can change seed crops and hence fitness of different species (Brudvig et al., 2015; Gómez‐Martínez et al., 2020). Recruitment success can be influenced by compositional changes to dispersers and predators of seeds in fragments (Almeida‐Neto et al., 2008; Galetti & Dirzo, 2013; Markl et al., 2012; Menke et al., 2012; Paine & Beck, 2007), for example, loss of large‐bodied dispersers or increased abundance of rodents.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, this caveat highlights the wealth of community interactions that underpin all plant-pollinator network links and are essential to pollinator health and plant reproduction alike. These unsung contributors range from larval food sources and breeding sites [113,114] to competitors for floral resources [115,116], to predators and parasites lurking within flowers [10,117,118]. Likewise, herbivores can have indirect effects on pollinator health through induced changes in floral resource quality [16,[119][120][121].…”
Section: (D) Resolving the Conflicts Inherent To Pollinating Herbivoresmentioning
confidence: 99%